1995
DOI: 10.1128/jvi.69.4.2341-2350.1995
|View full text |Cite
|
Sign up to set email alerts
|

Bovine papillomavirus E1 protein binds specifically DNA polymerase alpha but not replication protein A

Abstract: Extracts prepared from either mouse cells or monkey cells were examined for the ability to support in vitro bovine papillomavirus type 1 (BPV1) DNA replication, and they were used in parallel as a source of host replication proteins for affinity chromatography. DNA synthesis exhibited an absolute requirement for BPV1 E1 protein. In contrast to previous observations, we found that low levels of E1 were highly efficient in initiating DNA replication in the absence of the BPV1 transcription factor E2. Surprisingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
39
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 53 publications
3
39
0
Order By: Relevance
“…Biological materials. The cell lines employed for preparing soluble extracts for cell-free replication, the recombinant baculoviruses used for expressing the BPV1 proteins into Sf9 cells, and the antibodies able to recognize these proteins were described previously (4,42,44).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Biological materials. The cell lines employed for preparing soluble extracts for cell-free replication, the recombinant baculoviruses used for expressing the BPV1 proteins into Sf9 cells, and the antibodies able to recognize these proteins were described previously (4,42,44).…”
Section: Methodsmentioning
confidence: 99%
“…Expression and purification of viral proteins. BPV1 E2 and the glutathione S-transferase-E1 fusion protein (GST-E1) were expressed by infecting Sf9 cells with the appropriate recombinant baculoviruses, as reported previously (4,43). In order to purify the E1 protein, GST-E1-infected cells were lysed by hypotonic shock and the nuclear fraction was extracted in a selective manner by a combination of a high concentration of salt, a high pH, and a high concentration of Mg, as described previously (3).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently it has been suggested that E2TA might facilitate the stepwise assembly of E1 into a multimeric complex akin to the hexameric form of simian virus 40 (SV40) large tumor antigen (T-ag), which assembles at the SV40 origin (5,7,9,22,24,35). Like T-ag, E1 is able to bind ATP (23,40), act as an ATPase-dependent DNA helicase (36,47), and bind DNA polymerase alpha (4), all properties thought to be important for E1's role in viral DNA replication.…”
mentioning
confidence: 99%